Some aspects of the reproductive biology of Labeo victorianus (Boulenger, 1901) from Kuja-Migori River basin, Kenya - Elijah Kembenya; Albert Getabu; James Njiru; Reuben Omondi (Journal of Fisheries, 2022)
Labeo victorianus is an endemic species to Lake Victoria basin and also a species threatened with extinction status. This study investigated reproductive biology of L. victorianus from Kuja- Migori River basin, Kenya with a view to determining the length weight relationship (LWR), condition factor, fecundity, egg diameter gonado-somatic index (GSI), length at 50% maturity (LM50) and sex ratio. Sampling was done by electrofishing from January 2018 to June 2019. The LWR showed a negative allometric pattern (p < 0.05). The mean condition factor for combined sexes was 1.02. Fecundity ranged from 47842 – 101902 eggs (mean ± SD: 83663 ± 2605 eggs) and correlated highly with body size (r2 = 0.9137). Egg diameter ranged from 0.5 – 0.7 mm. Mean GSI was 6.3 ± 1.6 and 2.8 ± 0.45 for females and males respectively. The LM50 was estimated at 18 cm total length (TL) and 20 cm TL for males and females respectively. Sex ratio did not differ from the expected 1:1. This species has a high fecundity with small sized eggs and males attain sexual maturity earlier than females. The findings of this study provide useful information towards sustainable conservation of L. victorianus in the Lake Victoria basin.